The Growth and N Retention of Two Annual Desert Plants Varied Under Different Nitrogen Deposition Rates - Cui, Xiaoqing; Yue, Ping; Wu, Wenchao; Gong, Yanming; Li, Kaihui; Misselbrook, Tom; Goulding, Keith; Liu, Xuejun (Frontiers in Plant Science, 2019)
Nitrogen (N) partitioning between plant and soil pools is closely related to biomass accumulation and allocation, and is of great importance for quantifying the biomass dynamics and N fluxes of ecosystems, especially in low N-availability desert ecosystems. However, partitioning can differ among species even when growing in the same habitat. To better understand the variation of plant biomass allocation and N retention within ephemeral and annual species we studied the responses of Malcolmia Africana (an ephemeral) and Salsola affinis (an annual) to N addition, including plant growth, N retention by the plant and soil, and N lost to the environment using 15N (double-labeled 15NH415NO3 (5.16% abundance) added at 0, 0.8, 1.6, 3.2 and 6.4 g pot-1, equivalent to 0, 15, 30, 60 and 120 kg N ha-1) in a pot experiment. Higher N addition (N120) inhibited plant growth and biomass accumulation of the ephemeral but not the annual. In addition, the aboveground:belowground partitioning of N (the R:S ratio) of the ephemeral decreased with increasing N addition, but that of the annual increased. The N input corresponding to maximum biomass and 15N retention of the ephemeral was significantly less than that of the annual. The aboveground and belowground retention of N in the ephemeral were significantly less than those of the annual, except at low N rates. The average plant-soil system recovery of added 15N by the ephemeral was 70%, significantly higher than that of the annual with an average of 50%. Although the whole plant-soil 15N recovery of this desert ecosystem decreased with increasing N deposition, our results suggested that it may vary with species composition and community change under future climate and elevated N deposition.